A novel electrolyte used in high working voltage application for electrical double-layer capacitor using spiro-(1, 1′)-bipyrrolidinium tetrafluoroborate in mixtures solvents. (10th November 2015) - Yu, Xuewen; Wang, Jing; Wang, Chenglin; Shi, Zhiqiang
Abstract: This paper is addressed on studying the electrolytes for electrical double layer capacitors with relatively high ionic conductivity and electrochemical stability for high energy density application. A systematic analysis of the electrochemical characteristics has been presented using spiro-(1, 1′)-bipyrrolidinium tetrafluoroborate (SBP-BF4 ) with 1.5 mol L −1 (M) in variety of solvent compositions including propylene carbonate (PC), ethylene carbonate (EC) and dimethyl carbonate (DMC), while the solvent mixtures are PC + DMC (1:1 in volume) and PC + DMC + EC (1:1:1 in volume). The physical properties and electrochemical performance of SBP-BF4 -based electrolytes are improved by tuning solvent mixtures compositions for high working voltage application. The binary solvent system of PC + DMC electrolyte exhibits lowest viscosity of about 3.14 mPa s, while the ternary solvent system of PC + DMC + EC electrolyte exhibits highest conductivity of about 18.08 mS cm −1 . The SBP-BF4 /PC-based electrolytes display excellent upper voltage hold capability about 3.5 V. The binary solvent system exhibits superior rate performance, when the charge cut-off voltage is lower than 3.2 V. The ternary solvent system exhibits superior rate performance than that of other two solvent systems electrolytes, when the charge cut-off voltage is higher than 3.2 V. The maximum energy density and power density of EDLCs using the ternary solvent system electrolyte are 41.5 Wh kg −1 and 17.0 kW kg −1, respectively. The spiral cylindrical capacitors based on ternary solvent system electrolyte exhibits better cycle performance than that of other two solvent system electrolytes at the high working voltages.